Education as a preparation for work : an investigation of an episode of mathematics curriculum development in Ireland based upon the participant objectivation methodology of Pierre Bourdieu - Evans, John (Trinity College (Dublin, Ireland). School of Education, 2000)
This work examines a specific curriculum development initiative - the mathematics element of the Leaving Certificate Applied programme introduced in the Republic of Ireland in 1995. Chapter One shows that the methodology of this work is intended to reconcile the subjective knowledge of practice (practical knowledge) with the objective knowledge revealed by research (scholarly knowledge) through a study of the type described by the sociologist Pierre Bourdieu as participant objectivation. The aims of this study are to apply Bourdieu's approach to the episode of curriculum developm ent given here as an object of enquiry situated within education as a preparation for work, and to consider the implications of this study for the teaching and learning of mathematics.
Keywords: Education, Ph.D.; Ph.D. Trinity College Dublin